Perencanaan Komunikasi Lingkungan Dalam Penanggulangan Abrasi di Kecamatan Bantan Kabupaten Bengkalis - Elsarena, Mai Sela Rosa; Yasir, Yasir; Arifudin, Arifudin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The aim of this research is to analyze how environmental communication works in preventing abrasion in the coastal area of ??Bantan sub-district, Bengkalis Regency. Abrasion caused damage to at least 40% of Indonesia's 81,000 km of coast. Most of the soil types on Bengkalis Island are organosol soils, namely soil types that contain a lot of organic matter. The beach on Bengkalis Island is a beach that is very prone to abrasion, because it is directly facing the open ocean. This research uses a qualitative descriptive research type. The research was conducted in Bantan District, Bengkalis Regency, Riau Province. In this research the technique used was a purposive technique. Data collection methods use observation, interviews and documentation methods. In this research, researchers used Huberman and Miles' interactive model in analyzing research data. The results of this research show that the government has carried out environmental communication planning in 3 stages, namely situation analysis and problem identification, analysis of participants involved, and development of communication strategies.